Nucleoid Associated Proteins: The Small Organizers That Help to Cope With Stress - Hołówka, Joanna; Zakrzewska-Czerwińska, Jolanta (Frontiers in Microbiology, 2020)
The bacterial chromosome (called the nucleoid) must be efficiently compacted to fit inside the small and crowded cell while remaining accessible for the protein complexes involved in replication, transcription, and DNA repair. The dynamic organization of the nucleoid is a consequence of both intracellular factors (i.e., simultaneously occurring cell processes) and extracellular factors (e.g., environmental conditions, stress agents). Recent studies have revealed that the bacterial chromosome undergoes profound topological changes under stress. Among the many DNA-binding proteins that shape the bacterial chromosome structure in response to various signals, NAPs (nucleoid associated proteins) are the most abundant. These small, basic proteins bind DNA with low specificity and can globally influence chromosome organization (i.e., by coating the chromosome in response to stress) or regulate the transcription of specific genes (e.g., those involved in virulence).